If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -8(x + -3) = 5(x + 9) + 7 Reorder the terms: -8x + -8(-3 + x) = 5(x + 9) + 7 -8x + (-3 * -8 + x * -8) = 5(x + 9) + 7 -8x + (24 + -8x) = 5(x + 9) + 7 Reorder the terms: 24 + -8x + -8x = 5(x + 9) + 7 Combine like terms: -8x + -8x = -16x 24 + -16x = 5(x + 9) + 7 Reorder the terms: 24 + -16x = 5(9 + x) + 7 24 + -16x = (9 * 5 + x * 5) + 7 24 + -16x = (45 + 5x) + 7 Reorder the terms: 24 + -16x = 45 + 7 + 5x Combine like terms: 45 + 7 = 52 24 + -16x = 52 + 5x Solving 24 + -16x = 52 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 24 + -16x + -5x = 52 + 5x + -5x Combine like terms: -16x + -5x = -21x 24 + -21x = 52 + 5x + -5x Combine like terms: 5x + -5x = 0 24 + -21x = 52 + 0 24 + -21x = 52 Add '-24' to each side of the equation. 24 + -24 + -21x = 52 + -24 Combine like terms: 24 + -24 = 0 0 + -21x = 52 + -24 -21x = 52 + -24 Combine like terms: 52 + -24 = 28 -21x = 28 Divide each side by '-21'. x = -1.333333333 Simplifying x = -1.333333333
| 36=3u+6(u-3) | | -9-x=-6(2x+7) | | -5x+4x+20-10x= | | -11=7y+8(y+8) | | -22+6r=-8r-6(1-r) | | 2a+a=-21 | | (750-x)-600-y=3x-y | | 120.08=2808.97(r) | | (2y-80)=(y+9) | | 7(d-3)+6= | | (8x+12)=(10x-24) | | 3x-4+4x+8+x=180 | | (x+30)=(2x) | | 7x-4x+x-4+3x= | | 6.5x-5+x-1.2= | | 4b-6-9b-8= | | 682/d=21 | | (3x-15)=(2x+25) | | -5=5x+5y | | 50(t)=-16t^2+50o | | 50(t)=-16t^2+ho | | h(t)=-16t^2+ho | | 2(-8)-21(-8)-7= | | 25-15(-8)= | | 45=9/2h | | 25-15(8)= | | 45=1/2h(9) | | 2(8)-21(8)-7= | | ×=2/3 | | 9/7(M-19) | | -2x+3=5x-2 | | 7x^9/8-35=0 |